Impact of vitamin D deficiency on fluctuation of calcium and parathyroid hormone levels in postmenopausal osteoporosis - Tatjana Milivojac; Nela Rašeta; Vera Aksentić; Milkica Grabež (University of Banja Luka, Faculty of physical education and sport, 2015)
The primary role of vitamin D is regulation of calcium, phosphorus and bone metabolism. Vitamin D status assessment is based on measuring of 25 (OH) D concentrations, and disorders of vitamin D status may be manifested as a vitamin D insufficiency, vitamin D deficiency and vitamin D hypervitaminosis. It is generally accepted that values above 75 nmol / L will suffice to prevent the occurrence of secondary hyperparathyroidism. Although vitamin D deficiency can be found at any age, it is most common in women with postmenopausal osteoporosis, and in older women. The aim of this study was to determine the vitamin D status, parathyroid hormone levels and calcium levels in women with newly diagnosed postmenopausal osteoporosis, and to compare the results with the same parameters observed and measured in women without osteoporosis, and to establish whether there is a connection between vitamin D levels and levels of other parameters. The study involved 85 postmenopausal women, all of which were screened for osteoporosis by measuring bone mineral density in the lumbar spine and hip region using DXA method. Of these, 50 women were found to have osteoporosis while 35 had regular DXA values. Our results showed a high incidence of vitamin D deficiency in postmenopausal women, with significantly higher vitamin D deficiency in women with osteoporosis. The values of parathyroid hormone were higher, and the values of ionized calcium were lower in women with osteoporosis, and there is a negative correlation between 25 (OH) D and parathyroid hormone. The most common risk factors for osteoporotic fracture in postmenopausal women were early menopause and previous fracture in adulthood. Reduced levels of vitamin D in women with postmenopausal osteoporosis leads to changes in calcium and parathyroid hormone metabolism.